A Qualitative Exploration of Gaps and Challenges in Knowledge and Practices of Electroconvulsive Therapy by Key Personnel in Public and Private Mental Health Units in Kenya - Ali, Nabila Amin; Owiti, Frederick; Kigamwa, Pius; Kumar, Manasi (Frontiers in Psychiatry, 2019)
Background: Evidence-based research for electroconvulsive therapy (ECT) practice in Kenya is scarce. This has seemingly stifled knowledge with regard to ECT practice among key personnel in the country. Research shows that evidence-based guidelines not only harmonize clinical practice in a certain region but also improve health outcomes and quality of clinical decisions made by key personnel. This study aimed at assessing knowledge and administration of ECT by key personnel in psychiatric units in Kenya. Method: This is a qualitative study targeting multiple stakeholders in mental health facilities. The study was undertaken in three counties: Nairobi, Nakuru and Eldoret. Snowballing sampling method was used to interview 33 targeted respondents who work in ECT departments or actively interacted with the procedure in both private and public facilities. Researcher-designed respondent profile questionnaire and interview guides focusing on knowledge, practice and barriers in delivery of ECT were used as tools. Data collected were transcribed from the audio recordings. Thematic and content analyses of these semi-structured interviews were carried out based on the patterns that were noted across the data collected. The interviews were read by the research team and re-read to highlight the core ideas. Findings were presented in form of themes, which were illustrated along with representative verbatim quotations. Results: Overall, the key personnel were knowledgeable about ECT in different stages of the procedure, but we noticed methodological incongruence in their practice with regard to the pre-ECT preparation, stimulus dose calculation adequacy of seizure and in the procedure for dose adjustment of psychotropic medication before and after ECT sessions. The identified barriers to the uptake of evidence-based practice were lack of infrastructure, inadequate funding, lack of adequate training and negative perception by patients, relatives and even some participants. Conclusion: Though key personnel in this study showed that they had knowledge on ECT administration, lack of standard guidelines on ECT practice led to lack of standardized training on the procedure hence the methodological incongruence. Inadequate infrastructure, knowledge and negative perception towards the procedure seemed to interfere with uptake of ECT as an intervention. Recommendations: The study makes the following recommendations: adoption of a guideline by psychiatrists, intense training on ECT, specialized training for nurses in ECT and dose calculation for psychiatrists and registrars. Funding should be made available for new ECT machines. Lastly, education and awareness creation should be done about ECT to help deal with negative perception towards the intervention.